2022
DOI: 10.1186/s12889-022-13345-z
|View full text |Cite
|
Sign up to set email alerts
|

US soldiers and the role of leadership: COVID-19, mental health, and adherence to public health guidelines

Abstract: Background Previous studies have documented the impact of domain-specific leadership behaviors on targeted health outcomes in employees. The goal of the present study was to determine the association between specific leadership behaviors addressing COVID-19 and US soldiers’ mental health and adherence to COVID-19 public health guidelines. Methods An electronic, anonymous survey was administered to US Army soldiers across three major commands (N = 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In addition, this study showed that specific quarantine-related risk and resilience factors are related to mental health in the short and long term, in particular, “clear communication of the quarantine protocol” and “perceived stigma.” The positive message is that one main predictor can be easily addressed: the clear communication of the quarantine protocol, including the purpose and the rules of quarantining. While health-promoting leadership is not the over-arching main predictor or moderator of mental health during the COVID-19 pandemic as in a survey of 7,829 US Army personnel ( 27 ), it is also positively related to mental health as it is to the predictive resilience factors of perceived social support, perceived unit cohesion, and clear communication of the quarantine protocol (see Table in Supplementary material 5 ). While directly influencing the more general resilience factors of perceived social support and perceived unit cohesion might be difficult, health-promoting leadership, involving clearly communicated information and addressing the practicalities of quarantining, is recommended as one important entry point to facilitate the health protective factors of perceived unit cohesion and perceived social support and mental health.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, this study showed that specific quarantine-related risk and resilience factors are related to mental health in the short and long term, in particular, “clear communication of the quarantine protocol” and “perceived stigma.” The positive message is that one main predictor can be easily addressed: the clear communication of the quarantine protocol, including the purpose and the rules of quarantining. While health-promoting leadership is not the over-arching main predictor or moderator of mental health during the COVID-19 pandemic as in a survey of 7,829 US Army personnel ( 27 ), it is also positively related to mental health as it is to the predictive resilience factors of perceived social support, perceived unit cohesion, and clear communication of the quarantine protocol (see Table in Supplementary material 5 ). While directly influencing the more general resilience factors of perceived social support and perceived unit cohesion might be difficult, health-promoting leadership, involving clearly communicated information and addressing the practicalities of quarantining, is recommended as one important entry point to facilitate the health protective factors of perceived unit cohesion and perceived social support and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…As for specific military resilience factors during the COVID-19 pandemic, the few existent studies only based on US military service personnel showed that perceived unit cohesion, supportive leadership, and health-promoting leadership lessened the risk for reporting PTSD and anger, and clinically significant anxiety and depression ( 22 , 24 , 27 ), regardless of the personnel’s active response to the pandemic ( 22 ). Coping style and regulatory focus were identified as individual resilience factors for Chinese military officers during the COVID-19 pandemic ( 28 ).…”
Section: Introduction: German Armed Forces and The Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…mental health (Lopez et al, 2019). Moreover, studies have identified associations between specific leadership behaviors that target key domains and better outcomes, over and above general leadership skills (Adler et al, 2014(Adler et al, , 2022Gunia et al, 2015).…”
mentioning
confidence: 99%
“…Within the U.S. Army, leaders may have a critical role to play in preventing moral injury, given that soldiers’ perceptions of their leader’s general effectiveness are known to be associated with better mental health (Lopez et al, 2019). Moreover, studies have identified associations between specific leadership behaviors that target key domains and better outcomes, over and above general leadership skills (Adler et al, 2014, 2022; Gunia et al, 2015).…”
mentioning
confidence: 99%